Analyzing the Competitiveness and Complementarity of the Tea Trade between China and Mekong River Basin Countries - Yang, Wei; Mohammad Affendy, Arip; Chin Hong, Puah (IJEFI, 2025)
This study examines the competitiveness and complementarity of the tea trade between China and Mekong River Basin countries (Cambodia, Myanmar, Thailand, Vietnam, and Laos) from 2014 to 2023. Using the Revealed Comparative Advantage (RCA) index, the Trade Complementarity Index (TCI), and the Trade Intensity Index (TII), the research assesses China’s position in the tea market of the region. The survey results indicate that China has maintained a strong comparative advantage in tea exports, occupying a dominant position in the region, but competition from Vietnam is particularly significant. China’s tea trade exhibits strong complementarity with Cambodia and Myanmar while maintaining close trade ties with Vietnam, Cambodia, and Thailand. Recent trade complementarity and trade intensity between China and the Mekong River Basin countries show a steady upward trend, signaling increased alignment in bilateral trade. The study offers policy recommendations—adopting market-specific strategies, fostering regional cooperation, and optimizing product structures—to enhance China’s tea trade competitiveness.